Evaluasi Pembelajaran PAI sebagai Upaya Rekonstruksi Pendidikan Islam di Era Society 5.0 - Aryaningsih, Sri Panca; Suhirman; Abdul Fattah; Fathurrahman Muhtar; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to evaluate the implementation of Islamic Religious Education (PAI) learning as an effort to reconstruct Islamic education in the era of Society 5.0, and to identify factors that support and hinder the effectiveness of learning. The study uses a qualitative approach with a library research type. Data were obtained from various primary and secondary sources in the form of scientific books, journal articles, research results, and academic documents relevant to the evaluation of PAI learning, Islamic education, and Society 5.0. Data analysis was conducted using content analysis techniques through the stages of data reduction, data presentation, interpretation, and drawing conclusions. The results show that the evaluation of PAI learning is still dominated by the assessment of cognitive aspects, while the affective, psychomotor, and spiritual aspects have not been evaluated systematically and continuously. This condition causes the evaluation to be unable to fully measure the achievement of the goals of Islamic education oriented towards the formation of a perfect human being. In addition, the effectiveness of PAI learning in the era of Society 5.0 is supported by the use of digital technology, students' digital literacy, and learning innovation, but is still hampered by the low digital competence of teachers, limited infrastructure, and the less than optimal integration of religious and technological competencies. This research proposes the concept of digital-religious character evaluation as a model for reconstructing Islamic education that is relevant to the needs of a digital society and remains grounded in Islamic values.